Positive perception of pharmacogenetic testing for psychotropic medications. (7th March 2014) - Lanktree, Matthew B.; Zai, Gwyneth; VanderBeek, Laura E.; Giuffra, Daniel E.; Smithson, David S.; Kipp, Lucas B.; Dalseg, Timothy R.; Speechley, Mark; Kennedy, James L.
<x xml:space="preserve">Abstract</x> Introduction Pharmacogenetics attempts to identify inter‐individual genetic differences that are predictive of variable drug response and propensity to side effects, with the prospect of assisting physicians to select the most appropriate drug and dosage for treatment. However, many concerns regarding genetic tests exist. We sought to test the opinions of undergraduate science and medical students in southern Ontario universities toward pharmacogenetic testing. Methods and Results Questionnaires were completed by 910 undergraduate medicine and science students from 2005 to 2007. Despite students' concerns that the results of genetic tests may be used for other purposes without consent (71%) or lead to discrimination (78%), an overwhelming number of students were in favor of pharmacogenetic testing (90%). Discussion To our knowledge, this study is the first to survey a large sample for their attitude toward pharmacogenetic testing for psychotropic medications. Our results indicate that, although concerns remain and scientific advancements are required, respondents were in support of pharmacogenetic testing for medications used to treat schizophrenia. © 2014 The Authors. Human Psychopharmacology: Clinical and Experimental published by John Wiley & Sons, Ltd.